Sodium uptake and transport regulation, and photosynthetic efficiency maintenance as the basis of differential salt tolerance in rice cultivars - Gadelha, Cibelle Gomes (2022)
Rice (Oryza sativa L.) is among the most consumed cereals in the world. Its growth is severely affected by excessive salinity, leading to considerable negative economic impacts. Thus, BRS Esmeralda and Sao ˜ Francisco rice cultivars, presenting antagonist cultivation recommendations and differential salt tolerance, were selected to examine how salt stress influences ionic homeostasis and photosynthetic capacity. Phenotypic, physiological, molecular, and morphological results indicated that S˜ ao Francisco had a better potential to withstand salt stress than BRS Esmeralda. Although salinity promoted a significant increase in Na+ content, particularly in BRS Esmeralda, the harmful effects were less severe in Sao ˜ Francisco. The upregulation of SOS and NHX gene expressions revealed that Sao ˜ Francisco used these mechanisms to control Na+ accumulation in cytosol. Besides, Sao ˜ Francisco plants were efficient in reducing the adverse effects of salinity on photosynthesis. Under salt stress, Sao ˜ Francisco leaves exhibited better effective quantum efficiency of PSII, photochemical extinction coefficient, and electron transport rate. Besides, the relative energy excess in PSII and non-photochemical quenching were both smaller compared to BRS Esmeralda. Na+ cytotoxic effects damaged the chloroplast ultrastructure in BRS Esmeralda, reducing photosynthetic capacity. In contrast, the S˜ ao Francisco cultivar’s better performance was followed by an efficient Na+ exclusion and photosynthetic capacity maintenance, leading to lower growth losses. Overall, the findings are suitable for understanding salt responses and developing functional markers associated with salt stress tolerance improvement in rice.